Implementasi Metode Video Critic Untuk Menumbuhkan Minat Belajar Sejarah Kebudayaan Islam Pada Kelas VII di MTs Ma’arif NU 2 Cilongok - Khoirul Muna, Daffa (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2025)
Students’ interest in learning Islamic Cultural History tends to be low due to monotonous teaching methods. Conventional teaching dominated by lectures often fails to involve students actively. This study aims to describe the implementation of the Video Critic method in fostering students’ learning interest in Islamic Cultural History subjects at MTs Ma’arif NU 2 Cilongok. This research employed a qualitative descriptive approach with data collected through observation, interviews, and documentation. The research subjects included Islamic Cultural History teachers and seventh-grade students. The results showed that the implementation of the Video Critic method was carried out through three stages: planning, implementation, and evaluation. The planning stage involved preparing lesson plans and selecting videos relevant to the material. During the implementation stage, students watched educational videos, analyzed content, participated in group discussions, and presented their findings. Evaluation was conducted through observation of student engagement and assessment of discussion outcomes. This method effectively increased students’ learning interest by creating an engaging, interactive, and enjoyable learning atmosphere. Students became more enthusiastic, confident in expressing opinions, and showed increased interest in the subject. Therefore, the Video Critic method can serve as an alternative teaching strategy to enhance student participation and learning motivation.